Transient Analysis on Switching Capacitor Bank Using Power Factor Regulator - Alka Warizmi; Indra Roza; Ahmad Yanie (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
This study discusses the analysis of transients that occur in capacitor bank switching using a power factor regulator (PFR). Electric power systems use capacitor banks to offset reactive power, enhance power factors, and minimize energy losses. However, the switching process in capacitor banks can cause significant voltage and current spikes, known as transient phenomena, which can damage equipment and disrupt system stability. This study conducts simulations and analyzes the impact of transients that occur during the capacitor bank switching process on the electric power system. The simulation is carried out using software that models the behavior of the electric power system, focusing on how the power factor regulator regulates the switching process and its impact on the resulting transients. The simulation results show that the use of PFR can reduce the negative impact of transients, but improper settings can still cause disturbances that have the potential to damage the system. These findings provide important insights for system engineers in designing and operating more reliable power systems, considering the importance of proper settings on the power factor regulator to minimize the effects of transients on capacitor bank switching. This study also recommends several mitigation strategies to reduce the impact of transients and improve overall system stability.